Integrin–TGF-β crosstalk in fibrosis, cancer and wound healing - Margadant, Coert (Nature Publishing Group, 2010)
Accumulating evidence indicates that there is extensive crosstalk between integrins and TGF-β signalling. TGF-β affects integrin-mediated cell adhesion and migration by regulating the expression of integrins, their ligands and integrin-associated proteins. Conversely, several integrins directly control TGF-β activation. In addition, a number of integrins can interfere with both Smad-dependent and Smad-independent TGF-β signalling in different ways, including the regulation of the expression of TGF-β signalling pathway components, the physical association of integrins with TGF-β receptors and the modulation of downstream effectors. Reciprocal TGF-β–integrin signalling is implicated in normal physiology, as well as in a variety of pathological processes including systemic sclerosis, idiopathic pulmonary fibrosis, chronic obstructive pulmonary disease and cancer; thus, integrins could provide attractive therapeutic targets to interfere with TGF-β signalling in these processes.